Chapter Mediazioni e contaminazioni del modello dantesco nelle Montagne di Petar Zoranić (1508-1569?) - Cale, Morana (Biblioteca di Studi di Filologia Moderna, 2022)
The present paper is dedicated to 16th-century Croatian author Petar Zoranić's (Zadar / Zara, 1508 - 1569?) direct and mediated echoing of Dante's oeuvre. Zoranić's pastoral novel Planine (Mountains) belongs to the consistent tradition of reuse, quotation and translation that the Italian poet's legacy has enjoyed in Croatia from the 14th century to the present day. Building on the work of the humanist writer Marko Marulić (Marcus Marulus Spalatensis, Split / Spalato, 1450-1524), who aspired to do for the Croatian vernacular what Dante did for the Italian volgare, Zoranić adapted Dante's example to his own purposes not only in the promotion of the Croatian language and literature, but also in the celebration of the beauty, history and cultural heritage of his homeland. A true connoisseur of Dante's original, the author from Zadar was also competent in the art of appropriation and creative reemployment of the Commedia's various aspects, an exercise inaugurated by Boccaccio, and practiced by 15th and 16th-century men and women of letters. My contribution will focus on the modalities through which the text of Planine transforms the materials derived from Dante by mixing them with elements from other prestigious literary sources, in their turn heirs or precursors of Dante, such as works by Virgil, Ovid, the Church doctors, the Roman de la rose, Petrarch's Trionfi, the Decameron and the early narrative production by Boccaccio, Arcadia by Sannazaro and, according to my hypothesis, the Hypnerotomachia Poliphili (Polifilo's Dream) by Francesco Colonna.